Analysis of Milkfish Pond (Chano ANALISIS USAHA TAMBAK IKAN BANDENG (Chanos chanos) DI KELURAHAN KAMPUNG BARU KECAMATAN PENAJAM KABUPATEN PENAJAM PASER UTARA : Muhammad Arkan, 2022. Analysis of Milkfish Pond (Chanos chanos) in Kampung Baru Village, Penajam District, Penajam Paser Utara Regency (Supervised by: Bambang Indratno Gunawan and Nurul Ovia Oktawati). - Muhammad Arkan; Bambang Indratno Gunawan; Nurul Ovia Oktawati (2339-1324, 2023)
The purpose of the study was to analyze costs, revenues, and business feasibility, as well as to find out the constraints on the milkfish pond business. The research was carried out from July 2021 to August 2022 in Kampung Baru Village, Penajam District, North Penajam Paser Regency. The samples taken were 19 milkfish farmers by referring to the census method. The results showed that the cost and income of the milkfish pond business in Kampung Baru Village obtained an average production cost of Rp. 6.522.256/ha/MP, then the farmers' income is Rp. 1.358.994/ha/MP. The feasibility analysis of milkfish ponds shows that the R/C ratio is 1.20/ha/MP, Production BEP is 362 kg/ha/MP, BEP Price is Rp. 14.756/ha/MP and BEP Sales is Rp. 1.915.551/ha/MP, so that the milkfish pond business in Kampung Baru Village is feasible to run. The biggest obstacle in the milkfish pond business in Kampung Baru Village is the high price of fertilizer to support the growth of the milkfish's natural feed.